Arginase Production in Wild-Collected Neurospora crassa isolate from Lagos, Nigeria - Olubunmi Temitope, Aina; Busayo Tosin, Akinyemi; Ayodeji Adebola, Odunsi; Imade Yolanda, Nsa (Covenant Journal of Physical and Life Sciences, 2020)
There are inadequate records of wild-isolated Neurospora crassa from Nigeria. Most of the isolates reported are from air spores outdoors, and indoor environment of buildings including laboratories where it is a contaminant. A wild strain of N. crassa isolated from soil on a burned site was assayed for an important pharmaceutical metabolite, arginase. This isolate was identified by traditional cultivation methods and by its ribosomal DNA internal transcribed spacer (rDNA-ITS) sequence. Its average daily growth rate was 3.2 cm and as typical with N. crassa, it utilised different carbon sources. Among the sugars tested, sucrose, lactose, glucose and glycerol yielded the most biomass while ethanol supported the least growth. Arginase activity was determined by the amount of urea produced per unit time and its activity in the newly isolated N. crassa strain peaked on the second day and declined steadily thereafter in the course of five days.